A Liouville theorem for some Bessel generalized operators. Issue 5 (4th May 2018) - Galli, Vanesa; Molina, Sandra; Quintero, Alejandro
ABSTRACT: In this paper we establish a Liouville theorem inH μ ′ for a wider class of operators in( 0, ∞ ) n that generalizes the n -dimensional Bessel operator. We will present two different proofs, based in two representation theorems for certain distributions 'supported in zero'.